Safety Culture in Context: Macro and Micro Level Factors Affecting its Perception and Implementation: A Qualitative Inquiry (The International Journal of Engineering & Information Technology (IJEIT), 2025)
Safety culture assessment is an essential tool of organizational safety and has become mandatory in the aviation industry. A positive safety culture is a key for sustaining optimal safety performance in organizational safety. Most safety culture assessment tools are based on studies conducted in developed countries. However, safety culture assessment in developing countries, such as Arab countries is rarely examined in the aviation context. Semi-structured interviews with 14 technicians and managers in an aircraft maintenance organization based in an airport in an Arab country were conducted. These interviews discussed several topics related to occupational health and safety and safety management in aviation. The interview questions were designed based on a comprehensive examination of previous research on safety culture. The data obtained from the interview transcripts were categorized, resulting in a data structure that employed participants' quotes as primary codes and ultimately leading to the identification of three overall categories: Management commitment to safety, organizational safety practices, and role of social relationships. This study draws special attention to the influence of micro level internal factors of management commitment and organizational safety practices, and macro level external factors of the role of social relationships on the successful implementation of safety culture. Understanding the elements explored in this study offers a useful tool for distinguishing between various contextual elements and the level at which they operate. This could enable more effective management of these factors to improve the potential implementation of effective safety management.